Computer conferencing : its potential role in Caribbean science and technology information exchange - Black, John B. (UNESCO CaracasVE, 1985)
Discusses concept of computer conferencing and describes the telecommunications environment in the Caribbean focusing particularly on Jamaica, Antigua, St Lucia, Barbados, and Trinidad and Tobago. Highlights areas of current applications of computer conferencing and identifies factors essential to the successful application of same. Discusses the prospect for computer conferencing in the Region especially in the CARSTIN context. Lists other possible subject areas for computer conferencing in the Region.